Drought periods during 18th century in central Chile (33°S): A historical reconstruction perspective revisiting Vicuña Mackenna's work. (30th October 2018) - Jana, Patricia; Torrejón, Fernando; Araneda, Alberto; Stehr, Alejandra
Abstract : Understanding past climate variability is important for obtaining better predictions of future changes. Documentary records are high temporal resolution proxies that can be used to reconstruct aspects of the climate, such as precipitation. Vicuña Mackenna developed a compilation of historical climatic events between the 16 th and 19 th centuries using chronicles from Spanish colonizers and town council records. The objective of this work was to classify dry and wet periods beginning in the 16 th century using records from Vicuña Mackenna by generating a precipitation index based on events in the documentary evidence (e.g., epidemics, "pro pluvia" rogations, and infrastructural damage) into a simple annual precipitation index on an ordinal scale. The index used a three‐term classification scale, with 0 representing normal years, 1 representing wet years, and −1 representing dry years. The documentary records were not substantial enough to identify wet/dry periods during the 16 th and 17 th centuries. However, it was possible to identify dry and wet years described by conquerors and settlers that first arrived in the study area. During the 18 th century, two long periods of drought were identified: 1705 to 1718 and 1770 to 1797. During these droughts, people organized rogations to the Virgen and different saints in desperation due to the lack of water. Finally, during the 19 th century, technological improvements in measuring precipitation made it possible to identify intermittent dry and wet periods with higher resolution and precision, and these events could be related to the El Niño–Southern Oscillation (ENSO). Abstract : The objective of this work was to classify dry and wet periods since the 16 th century using Vicuña Mackenna's records by generating a precipitation index based on the transformation of documentary evidence into a simple annual precipitation index. The classification scale used was 0 for normal years, 1 for wet years, and −1 for dry years. During the 18 th century it identified two long periods of droughts that are not fully recorded in literature.